Method for measuring fiber length in fiber reinforced thermoplastic composite material
By mixing the fiber-reinforced thermoplastic composite material with the thermoplastic resin and molding it into a sample, the fiber length is measured under an optical microscope, which solves the accuracy and reproducibility of fiber length measurement in the prior art, improves the measurement efficiency and is suitable for multiple applications. This fiber type achieves higher measurement accuracy and safety.
Patent Information
- Application Number
- CN202411282542.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, the fiber length measurement method of fiber reinforced thermoplastic composite material has problems such as poor accuracy and reproducibility of measurement results, and low measurement efficiency.
Mix fiber-reinforced thermoplastic composite with thermoplastic resin to dilute, prepare diluent material and mold it into a test spline, cut it into a sample sheet, measure the length of the fibers in the sample sheet under an optical microscope, avoid high-temperature burning and solution dispersion operations, and directly observe the sample sheet. fiber length.
It improves measurement accuracy and reproducibility, reduces damage and deformation of fibers, shortens detection time, is suitable for a variety of fiber types, and is safe and environmentally friendly.
Smart Images

Figure CN119197327A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber size measurement, and in particular relates to a method for measuring fiber length in a fiber-reinforced thermoplastic composite material. Background Art
[0002] As a material with a high aspect ratio, reinforcing fiber is added as a filler to a thermoplastic polymer matrix resin to obtain a fiber-reinforced thermoplastic composite material, which can effectively improve the performance of the matrix resin and enable it to obtain superior mechanical properties and dimensional stability. Experimental studies have found that the various properties of the fiber-reinforced thermoplastic composite material are closely related to the fiber length in its matrix; on the one hand, a reasonable fiber length can better share the external stress on the matrix resin, delay the trend of crack development, and enable the matrix resin to obtain higher tensile strength, bending strength and impact strength; on the other hand, the fiber length will also affect the degree of fiber orientation during the processing of fiber-reinforced thermoplastic composite materials and the processing fluidity of the fiber-reinforced thermoplastic composite melt. Therefore, how to quickly and accurately measure the fiber length in fiber-reinforced thermoplastic composites is of great significance to the improvement of material processing technology and the prediction of performance.
[0003] At present, there are four main methods commonly used to measure the fiber length in fiber-reinforced thermoplastic composites: combustion method, dissolution method, copper mesh scooping method and indirect method. Among them, the combustion method is to calcine the fiber-reinforced thermoplastic composite at a certain temperature to fully decompose the matrix resin, dilute and disperse it with a solvent, and place it in a culture dish. Finally, use a microscope to observe and calibrate the fiber length. If it is directly calcined, it may come into contact with the air, which may easily cause the fiber to decompose or break. If an inert gas is used to protect the combustion process, the matrix resin decomposes very slowly, and it is easy to have residual decomposition products, which affects the subsequent sample preparation process; both calcination methods will make the test results inaccurate, and due to the different lengths of the fibers, if they are dispersed in water, the viscosity of the water is low, and the process of stirring and dispersing them in the culture dish will cause the longer fibers and the shorter fibers to be layered and other uneven phenomena, which will cause the measurement results to deviate greatly from the actual situation; if a viscous solution is used for dispersion, it needs to be fully stirred to make it evenly distributed, which may easily cause secondary fiber breakage, and ultimately cause the measurement results to deviate from the actual results. The dissolution method must strictly control the filtration pressure and speed during the fiber separation stage. Due to the use of porous filter paper, the fibers cannot be completely removed, and the removed fibers are difficult to be evenly distributed on the glass slide. These factors will lead to a large deviation between the test results and the actual situation. At the same time, the organic solvents used may also damage the integrity of the fibers, affecting the measurement results. The copper mesh scooping method has high requirements in terms of operating environment and operating precision. For example, when scooping samples, the angle of the copper mesh immersed in the sample solution, the scooping force and path, etc. must be strictly controlled. Otherwise, the film attached to the copper mesh will have uneven thickness, overlapping or damage when scooping. There is a lot of randomness in the sampling process, making it difficult to guarantee measurement accuracy and reproducibility. The indirect method often requires measuring parameters such as material tensile strength and modulus, and inferring the fiber length through mathematical models. This method is generally only used as a qualitative analysis and cannot accurately reflect the actual length of the fiber.
[0004] Chinese patent CN113447483A discloses a method for testing the fiber length in short fiber composite plastics, which is to calcine the sample to be tested in an inert gas, dissolve the pure fiber obtained after calcination in a viscous liquid, dry the pure fiber and then test it under a microscope. This method is improved on the basis of the traditional combustion method, and the fiber is protected by an inert gas to prevent it from being destroyed, and the viscous liquid is used to improve the dispersion of the fiber in the solution.
[0005] However, this patent has the following disadvantages: 1. In an inert gas environment, resin materials are difficult to degrade and burn. If the resin material is an easily carbonized material (such as polycarbonate, polyphenylene sulfide, aromatic polyamide), it usually takes dozens of hours to degrade it to obtain a fiber sample, and it cannot be guaranteed that the non-fiber components are completely removed. On the one hand, the measurement efficiency is low, and on the other hand, the accuracy and reproducibility of the measurement results are difficult to guarantee; 2. In the process of preparing the fiber dispersion, it is necessary to undergo dispersion transfer and stirring operations, and because the liquid used in the dispersion is viscous, in order to ensure uniform dispersion and eliminate randomness, vigorous stirring is required. This results in the process of preparing the dispersion. The fiber is easily broken and deformed due to being exposed and unprotected, which causes the final fiber length test result to deviate.
[0006] Chinese patent CN109164106A discloses a method for testing the retained length of glass fibers in glass fiber reinforced thermoplastic composite materials. The method comprises the following steps: firstly calculating the theoretical mass of the glass fiber reinforced thermoplastic composite material required for testing a predetermined number of glass fibers, then burning the composite material of the theoretical mass to remove the resin to obtain a glass fiber sample, dispersing the obtained glass fiber sample by adding a solvent, and measuring the length of the glass fiber using a microscope and image analysis software after drying, wherein the predetermined number of fibers to be measured is 1000-100000.
[0007] However, this patent has the following disadvantages: 1. It is difficult to remove easily carbonized resins and flame retardant components by combustion, and the temperature usually needs to be raised to 900°C to effectively remove the above components, while the 600-650°C in this patent obviously does not meet the requirements; in addition, the combustion method will cause irreversible damage to carbon fibers or other polymer fibers, causing them to partially decompose and affect the measurement results of the length of carbon fibers or other polymer fibers; high temperatures above 600°C will also cause fibers with low softening points such as boron-free and fluorine-free glass fibers to twist and deform under stress, and the tortuous fiber state will affect the measurement results of the glass fiber length; 2. While removing the resin by burning in this patent, the impregnant on the surface of the glass fiber will also be removed. Glass fibers without impregnant protection are more brittle. In the process of dispersing the fibers, the glass fibers without impregnant protection will partially break, and finally Ultimately affecting the length measurement; 3. The reliability and reproducibility of the measurement data are not verified in this patent, and the variance of multiple measurement results is not analyzed. The reproducibility and accuracy of the measurement results cannot be proved by simply increasing the number of measured fibers; 4. The detection efficiency of the fiber length in this patent is low. The reason is that this patent requires the tester to manually calibrate and measure the length data of 1000-100000 fibers on the image analysis software to calculate and analyze the results. However, the current image analysis software cannot effectively identify the length of overlapping fibers, and most of the fiber samples obtained by this sample preparation method are in an overlapping state. By reducing the concentration of the fibers in the solution, the complete separation between the fiber samples can be approximately achieved, but this will cause the number of fibers in the field of view of the microscope to decrease sharply, and the solution needs to be moved multiple times for length calibration, so the measurement efficiency is low.
[0008] The above problems lead to low efficiency, inaccurate test results or poor reproducibility of fiber length measurement in fiber reinforced thermoplastic composites, which is not conducive to the adjustment of composite material formulation and process and the performance prediction of composite products. Therefore, the development of a fast, efficient, accurate and reproducible method for measuring fiber length in fiber reinforced thermoplastic composites is of great significance to the development and application of thermoplastic composites. Summary of the invention
[0009] The purpose of the present invention is to provide a method for measuring the fiber length in a fiber reinforced thermoplastic composite material, so as to solve the problems of poor measurement accuracy and reproducibility, as well as low measurement efficiency, in the current fiber length measurement method for fiber reinforced thermoplastic composite materials.
[0010] To achieve the above object, the technical solution adopted by the present invention is: The method for measuring the fiber length in the fiber-reinforced thermoplastic composite material of the present invention is to mix and dilute the fiber-reinforced thermoplastic composite material with a thermoplastic resin to obtain a diluted material, press the diluted material to obtain a test specimen, cut the test specimen into a sample, and measure the length of the fiber in the sample under an optical microscope; wherein the fiber-reinforced thermoplastic composite material is made of a matrix resin and reinforcing fibers, and the matrix resin is the same as the thermoplastic resin.
[0011] in: The matrix resin is one of polypropylene, polyamide, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polystyrene, polyphenylene sulfide, polysulfone, liquid crystal polymer, polyetheretherketone, polyvinyl chloride, polyethylene, polyoxymethylene or polyphenylene ether.
[0012] The thermoplastic resin is one of polypropylene, polyamide, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polystyrene, polyphenylene sulfide, polysulfone, liquid crystal polymer, polyetheretherketone, polyvinyl chloride, polyethylene, polyoxymethylene or polyphenylene ether.
[0013] The reinforcing fiber is one of glass fiber, carbon fiber, basalt fiber, silicon carbide fiber, polyphenylene sulfide fiber, polyimide fiber, silicon carbide whisker, potassium titanate whisker, aluminum borate whisker, calcium carbonate whisker, calcium sulfate whisker, aluminum oxide whisker or silicon nitride whisker.
[0014] The reinforcing fiber content in the diluent is 0.1-1wt%.
[0015] The magnification of the optical microscope is 50x-100x.
[0016] The test strip has a thickness of 0.1-1 mm, a length of 20-150 mm, and a width of 20-150 mm.
[0017] The sample has a length of 5-10 mm and a width of 5-10 mm.
[0018] The lengths of 50-200 fibers in the sample were measured under an optical microscope.
[0019] The method for measuring the fiber length in the fiber-reinforced thermoplastic composite material of the present invention comprises the following specific steps: S1. Weigh 1-100 g of the fiber-reinforced thermoplastic composite material for later use; S2. Calculate the weight of the required thermoplastic resin according to the ratio of 0.1-1wt% of the reinforcing fiber content in the dilution material; S3, weighing a required weight of thermoplastic resin, and blending it with the fiber-reinforced thermoplastic composite material for 5-10 minutes to obtain a diluted material; S4, molding the diluted material into samples to prepare test strips with a thickness of 0.1-1 mm, a length of 20-150 mm, and a width of 20-150 mm; S5. Cut the test specimen into samples with a length of 5-10 mm and a width of 5-10 mm, select 5-30 samples and label them; S6. Place 5-30 samples on glass slides respectively, place the glass slides under an optical microscope with a magnification of 50x-100x, adjust the focus, select 50-200 fibers from each sample, start measuring the fiber length and fiber distribution, and calculate the average fiber length.
[0020] The present invention avoids the difficulty of observation caused by high-density fiber distribution by preparing a sample with low reinforcing fiber density. The sample prepared by the present invention has good light transmittance due to its thin thickness, thereby ensuring that all kinds of thermoplastic resin composite systems can be directly observed and the fiber length can be measured using an optical microscope through this method. The present invention does not require high-temperature burning operations, avoids the decomposition and softening and bending deformation of the reinforcing fibers caused by high temperature, and reduces the sample preparation and observation time. The present invention does not require the use of a solution for dispersion, so there is no need to transfer and stir the fiber sample, avoiding inaccurate fiber length measurement caused by mechanical damage.
[0021] The beneficial effects of the present invention are as follows: 1. The present invention dilutes and molds the thermoplastic composite material into sheets, ensuring the visibility and integrity of the fibers: Dilution can effectively reduce fiber overlap; while molding into samples improves the orientation of the fibers, making it easier to calibrate the fiber length, while further fixing the position of the fibers and reducing fiber deformation and dislocation. Therefore, the visibility of the fibers can be ensured by dilution and molding into sheets. The present invention does not require the use of burning treatment or dispersion treatment in traditional measurement methods to ensure the visibility of the fibers. Compared with traditional measurement methods, on the one hand, it avoids fiber damage, deformation and breakage that may be caused by high temperature or solvents, and has higher measurement accuracy; on the other hand, the present invention is based on the dilution of the original resin system, does not produce phase changes and fiber aggregation, and can better reflect the true length and distribution of the fibers in the matrix, with better accuracy.
[0022] 2. The test efficiency of the present invention is higher and the reproducibility of the measurement results is good: compared with the existing fiber length measurement method, the present invention does not require calcination, dry dispersion, fiber separation and arrangement, or copper mesh scooping and other refined operations, which reduces the randomness of the measurement and improves the reproducibility of the measurement results. In addition, in the combustion method and the dissolution method, the concentration of the fiber in the dispersion medium can be reduced to achieve fiber separation, thereby improving the accuracy of the measurement results. However, when calibrating the fiber length, the movement of the dispersion medium will also cause the fibers in the dispersion medium to move slightly, and the observation angle needs to be adjusted from time to time, which reduces the test efficiency and is not conducive to the reproducibility of the measurement results. The present invention saves a lot of time required for refined operations such as calcination, dry dispersion, fiber separation and arrangement, or copper mesh scooping by preparing sample pieces, reduces sample preparation time, and improves detection efficiency; the fiber is fixed in the sample piece, and when calibrating the fiber length, it is only necessary to move the sample piece without adjusting the observation angle, thereby improving the test efficiency and the reproducibility of the measurement results.
[0023] 3. The present invention is safer and more environmentally friendly: Compared with the dissolution method that requires the use of solvents to dissolve samples or the copper mesh scooping method that requires the use of membrane support agents to assist in film formation, the present invention reduces the use and emission of volatile organic compounds, the operation process is green and environmentally friendly, and reduces the risk of damage to the health of operators. At the same time, compared with the dissolution method that requires the use of a dissecting needle to arrange the fibers on a glass slide during measurement, the present invention has no exposed fibers throughout the entire process, which can effectively prevent testers from being allergic or stabbed by fiber attachment, thereby improving work safety.
[0024] 4. The present invention has wide applicability: Since the present invention does not use operations that may destroy the fiber crystal structure, such as calcination and violent stirring, it is applicable to both crystalline thermoplastic systems and semi-crystalline thermoplastic systems. It is also applicable to various fiber types such as glass fiber, carbon fiber, basalt fiber, silicon carbide fiber, polyphenylene sulfide fiber and polyimide fiber, and has a wider range of adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a 100-fold optical microscope image of sample No. A-1 in Example 1.
[0026] Figure 2 This is a 50x optical microscope image of the sample No. B-1 in Example 2. DETAILED DESCRIPTION
[0027] The present invention is specifically described and illustrated below in conjunction with embodiments.
[0028] Example 1 Fiber-reinforced thermoplastic composite material: A glass fiber-reinforced PC composite material with a fiber content of 30wt% was selected and produced by Taishan Glass Fiber Co., Ltd.; the fiber-reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0029] Base resin: PC (polycarbonate), grade 120110, produced by LG Chemical of South Korea; Thermoplastic resin: PC, brand 120110, produced by LG Chemical of South Korea; Reinforcement fiber: Glass fiber, brand ECS10-3.0-T442, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0030] Weigh 10 g of the fiber-reinforced thermoplastic composite material for use; calculate the weight of the required thermoplastic resin according to the ratio of 0.3 wt% of the reinforcing fiber content in the dilution material, and obtain the mass of the required thermoplastic resin as 990 g; weigh 990 g of the thermoplastic resin, put it and 10 g of the fiber-reinforced thermoplastic composite material into a high-speed mixer and blend them for 5 minutes to obtain a dilution material; use a molding machine to press to prepare a test specimen with a thickness of 1 mm, a length of 150 mm, and a width of 150 mm; cut the test specimen into a sample with a length of 10 mm and a width of 10 mm, select 5 samples and place them on glass slides, numbered A-1 to A-5; Place 5 slides with samples under a 100x optical microscope. Select the transmission mode of the optical microscope. After adjusting the focus, measure the length and distribution of 100 fibers in each sample and calculate the average fiber length. The optical microscope image of the sample numbered A-1 is shown in Figure 2. Figure 1 As shown, the average fiber length is the average value of the lengths of 100 selected fibers. The three intervals of fiber length are selected as 0-0.3 mm, 0.3-0.6 mm and above 0.6 mm. The total number of fibers in each interval is counted respectively, and the percentage of the number of fibers in the three intervals to the total number is calculated. The data variance is also calculated. The specific data are shown in Table 1.
[0031]
[0032] Example 2 Fiber reinforced thermoplastic composite material: A glass fiber reinforced PP composite material with a fiber content of 30wt% is selected; it is produced by Taishan Glass Fiber Co., Ltd.; wherein the fiber reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0033] Base resin: PP (polypropylene), brand name Y2600T, produced by Sinopec Shanghai Petrochemical Co., Ltd.; Thermoplastic resin: PP, brand name Y2600T, produced by Sinopec Shanghai Petrochemical Co., Ltd.; Reinforcement fiber: Glass fiber, brand ECS10-3.0-T438G, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0034] Weigh 100 g of the fiber-reinforced thermoplastic composite material for use; calculate the weight of the required thermoplastic resin according to the ratio of 1 wt% of the reinforcing fiber content in the dilution material, and obtain the mass of the required thermoplastic resin as 2900 g; weigh 2900 g of the thermoplastic resin, put it and 100 g of the fiber-reinforced thermoplastic composite material into a high-speed mixer and blend them for 5 minutes to obtain a dilution material; use a molding machine to press to prepare a test specimen with a thickness of 0.5 mm, a length of 100 mm, and a width of 80 mm; cut the test specimen into a sample with a length of 10 mm and a width of 10 mm, select 5 samples and place them on glass slides, numbered B-1 to B-5; Place 5 slides with samples under a 50x optical microscope. Select the transmission mode of the optical microscope. After adjusting the focus, measure the length and distribution of 200 fibers in each sample and calculate the average fiber length. The optical microscope image of the sample numbered B-1 is shown in Figure 2. Figure 2 As shown in Table 2, the average fiber length is the average value of the lengths of 200 selected fibers. The three intervals of fiber length are selected as 0-0.3 mm, 0.3-0.6 mm and above 0.6 mm. The total number of fibers in each interval is counted respectively, and the percentage of the number of fibers in the three intervals to the total number is calculated. The data variance is also calculated. The specific data are shown in Table 2.
[0035]
[0036] Example 3 Fiber reinforced thermoplastic composite material: glass fiber reinforced PA66 composite material with a fiber content of 30wt% was selected; it was produced by Taishan Glass Fiber Co., Ltd.; the fiber reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0037] Base resin: PA66 (polyhexamethylene adipamide), brand EPR27LS, produced by Pingdingshan Shenma Engineering Plastics Co., Ltd.; Thermoplastic resin: PA66, brand EPR27LS, produced by Pingdingshan Shenma Engineering Plastics Co., Ltd.; Reinforcement fiber: glass fiber, brand ECS10-3.0-T435TM, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0038] Weigh 1 g of the fiber-reinforced thermoplastic composite material for use; calculate the weight of the required thermoplastic resin according to the ratio of 0.1 wt% of the reinforcing fiber content in the dilution material, and obtain the mass of the required thermoplastic resin as 299 g; weigh 299 g of the thermoplastic resin, put it and 1 g of the fiber-reinforced thermoplastic composite material into a high-speed mixer and blend them for 5 minutes to obtain a dilution material; use a molding machine to press to prepare a test specimen with a thickness of 0.1 mm, a length of 20 mm, and a width of 20 mm; cut the test specimen into a sample with a length of 5 mm and a width of 5 mm, select 5 samples and place them on glass slides respectively, and number them as C-1 to C-5; Five glass slides with samples were placed under an 80x optical microscope. The optical microscope was in transmission mode. After adjusting the focal length, the fiber length and fiber distribution of 50 fibers in each sample were measured, and the average fiber length was calculated. The average fiber length was the average of the lengths of the 50 selected fibers. The three intervals of fiber length of 0-0.3 mm, 0.3-0.6 mm, and above 0.6 mm were selected. The total number of fibers in each interval was counted, the percentage of the number of fibers in the three intervals to the total number was calculated, and the data variance was calculated. The specific data are shown in Table 3.
[0039]
[0040] Comparative Example 1 Fiber-reinforced thermoplastic composite material: A glass fiber-reinforced PC composite material with a fiber content of 30wt% is selected; it is produced by Taishan Glass Fiber Co., Ltd.; wherein the fiber-reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0041] Base resin: PC, brand 120110, produced by LG Chemical of South Korea; Reinforcement fiber: Glass fiber, brand ECS10-3.0-T442, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0042] The ceramic crucible was placed in a tube furnace and dehydrated at 500°C for 15 minutes. After being taken out, it was placed in a drying dish and cooled to room temperature. An appropriate amount of fiber-reinforced thermoplastic composite material was placed in the dried crucible, and the crucible was placed in a muffle furnace. After being calcined at 625°C for 3 hours, the crucible was taken out, placed in a drying dish, and cooled to room temperature. At this time, reinforcing fibers remained in the crucible. 0.02g of the reinforcing fibers in the crucible were taken, placed in a Petri dish, 20g of anhydrous ethanol was added, and stirred evenly. The Petri dish was placed on a heating plate at 60°C and heated until the liquid substance evaporated completely. The Petri dish was placed on the stage of a 50x microscope for observation, and 5 points of the field of view were randomly selected, labeled CA-1 to CA-5, and observed. 20 fibers were selected at each point to measure the fiber length and fiber distribution, and the average fiber length was calculated. The specific data are shown in Table 4.
[0043]
[0044] Comparative Example 2 Fiber reinforced thermoplastic composite material: A glass fiber reinforced PP composite material with a fiber content of 30wt% is selected; it is produced by Taishan Glass Fiber Co., Ltd.; wherein the fiber reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0045] Base resin: PP, brand Y2600T, produced by Sinopec Shanghai Petrochemical Co., Ltd.; Reinforcement fiber: Glass fiber, brand ECS10-3.0-T438G, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0046] The ceramic crucible was placed in a tubular furnace and subjected to anhydrous treatment at 500°C for 15 minutes. After being taken out, it was placed in a drying dish and cooled to room temperature. An appropriate amount of fiber-reinforced thermoplastic composite material was placed in the dried crucible, and the crucible was placed in a muffle furnace. After being calcined at 625°C for 3 hours, the crucible was taken out, placed in a drying dish, and cooled to room temperature. At this time, reinforcing fibers remained in the crucible. 0.02 g of the reinforcing fibers in the crucible were taken out and placed in a culture dish, 20 g of anhydrous ethanol was added, and stirred evenly. The culture dish was placed on a heating plate at 60°C and heated until the liquid substance evaporated completely. The culture dish was placed on the stage of a 50x microscope for observation, and 5 points of the field of view were randomly selected, labeled CB-1 to CB-5, and observed. 20 fibers were selected at each point to measure the average fiber length and length distribution range. The specific data are shown in Table 5.
[0047]
[0048] Comparative Example 3 Fiber-reinforced thermoplastic composite material: A glass fiber-reinforced PA66 composite material with a fiber content of 30wt% is selected; it is produced by Taishan Glass Fiber Co., Ltd.; wherein the fiber-reinforced thermoplastic composite material is made of matrix resin and reinforcing fiber.
[0049] Base resin: PA66, brand EPR27LS, produced by Pingdingshan Shenma Engineering Plastics Co., Ltd. Reinforcement fiber: glass fiber, brand ECS10-3.0-T435TM, produced by Taishan Glass Fiber Co., Ltd., with a short cut length of 3 mm.
[0050] The ceramic crucible was placed in a tubular furnace and subjected to anhydrous treatment at 500°C for 15 minutes. After being taken out, it was placed in a drying dish and cooled to room temperature. An appropriate amount of fiber-reinforced thermoplastic composite material was placed in the dried crucible, and the crucible was placed in a muffle furnace. After being calcined at 625°C for 3 hours, the crucible was taken out, placed in a drying dish, and cooled to room temperature. At this time, reinforcing fibers remained in the crucible. 0.02 g of the reinforcing fibers in the crucible were taken and placed in a Petri dish, 20 g of anhydrous ethanol was added, and stirred evenly. The Petri dish was placed on a heating plate at 60°C and heated until the liquid substance evaporated completely. The Petri dish was placed on the stage of a 50x microscope for observation, and 5 points of the field of view were randomly selected, labeled CC-1 to CC-5, and observed. 20 fibers were selected at each point to measure the average fiber length and length distribution range. The specific data are shown in Table 6.
[0051]
[0052] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the method for measuring the fiber length in the fiber-reinforced thermoplastic composite material described in Examples 1-3 of the present invention can effectively shorten the detection time of the fiber length in the fiber-reinforced thermoplastic composite material, and the multiple detection results obtained have the advantages of stability and small discreteness. The method is less destructive to the fibers during the sample preparation and observation process. The fiber lengths of Examples 1-3 measured using the measurement method of the present invention have good consistency and relatively uniform fiber distribution. It can more truly and accurately reflect the length and distribution of the reinforcing fibers in the fiber-reinforced thermoplastic composite material, and provide a real, intuitive and effective reference for the optimization of the production formula, process and equipment of the thermoplastic composite material.
Claims
1. A method for measuring fiber length in a fiber-reinforced thermoplastic composite material, characterized in that: The fiber-reinforced thermoplastic composite material is mixed and diluted with a thermoplastic resin to obtain a diluted material, the diluted material is pressed to obtain a test specimen, the test specimen is cut into samples, and the length of the fiber in the sample is measured under an optical microscope; wherein the fiber-reinforced thermoplastic composite material is made of a matrix resin and reinforcing fibers, and the matrix resin is the same as the thermoplastic resin.
2. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The matrix resin is one of polypropylene, polyamide, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polystyrene, polyphenylene sulfide, polysulfone, liquid crystal polymer, polyetheretherketone, polyvinyl chloride, polyethylene, polyoxymethylene or polyphenylene ether.
3. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The thermoplastic resin is one of polypropylene, polyamide, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polystyrene, polyphenylene sulfide, polysulfone, liquid crystal polymer, polyetheretherketone, polyvinyl chloride, polyethylene, polyoxymethylene or polyphenylene ether.
4. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The reinforcing fiber is one of glass fiber, carbon fiber, basalt fiber, silicon carbide fiber, polyphenylene sulfide fiber, polyimide fiber, silicon carbide whisker, potassium titanate whisker, aluminum borate whisker, calcium carbonate whisker, calcium sulfate whisker, aluminum oxide whisker or silicon nitride whisker.
5. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The reinforcing fiber content in the diluent is 0.1-1wt%.
6. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The magnification of the optical microscope is 50x-100x.
7. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The test strips have a thickness of 0.1-1 mm, a length of 20-150 mm, and a width of 20-150 mm.
8. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The length of the sample is 5-10mm and the width is 5-10mm.
9. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The lengths of 50-200 fibers in the sample were measured under an optical microscope.
10. The method for measuring fiber length in a fiber-reinforced thermoplastic composite material according to claim 1, characterized in that: The mixing and dilution time is 5-10 minutes.
Citation Information
Cited By
Method for detecting length of carbon fiber in carbon fiber composite material
CN121557870A
A method for detecting the length of carbon fibers in a carbon fiber composite material
CN121557870B